Cerium oxide nanoparticles, physical and chemical properties, applications and toxicological implications: A review - Mohammad Mohajeri; Reza Momenai; Somayyeh Karami-Mohajeri; Mandana Ohadi; Mohammad Amin Raeisi Estabragh (Results in Chemistry)
The use of engineered nanomaterials, specifically cerium oxide nanoparticles (CeO2 NPs), has raised concerns about their potential toxicity and interactions with biological and ecological systems. Due to their small size and large surface area-to-volume ratios, CeO2 NPs have unique physicochemical properties that can affect their behavior and toxicity. While these properties can be beneficial in biomedical and industrial applications, they can also increase cellular uptake, reactivity, and oxidative stress in living organisms. As a result, nanotoxicology has become an important interdisciplinary field at the intersection of nanotechnology, biology, and environmental science. However, the safety assessment of CeO2 NPs is still being investigated, as their ability to disperse and persist in environmental media such as water, soil, and air presents complex ecotoxicological challenges. Additionally, discrepancies in toxicity outcomes are often attributed to differences in synthesis methods, particle size distribution, surface modifications, and aggregation behavior. This review aims to provide a comprehensive overview of current research on the toxicity and environmental fate of CeO2 NPs, highlighting the relationship between their physicochemical properties and biological interactions, and emphasizing the need for standardized testing protocols to ensure reliable risk assessment.